Kajian Penerapan Sistem Pengelolaan Sampah dengan Pendekatan Metode 3R di Kabupaten Padang Pariaman - Rizki Aziz; Taufiq Ihsan; Datin Suhaila (Jurnal Dampak, 2020)
This study aims to determine the existing conditions of solid waste management in Padang Pariaman Regency and the problems faced, as well as to assess the potential of implementing a municipal solid waste management system using the reduce-reuse-recycle (3R) method through a 3R based Solid Waste Treatment Plant (3R-SWTP) for region scale and Integrated Solid Waste Treatment Plant (ISWTP) for the city scale as a solution to municipal solid waste problems. This study was conducted through surveys, observations and interviews with solid waste management institutions, collection of secondary solid waste management data and literature studies. From the survey, observation, and interview it was found that the solid waste generation of Padang Pariaman Regency was 1,396 m3/day and only 1,35% of the total solid waste was served. The problem of waste management faced were  the high amount of waste that is not served, the inadequate facilities and infrastructure for operational solid waste handling and the low level of solid waste minimization practices. Through the implementation of the 3R-SWTP and ISWTP-based solid waste management system, it is estimated that it will be able to minimize the city solid waste by 23% by operation of 7 unit of 3R-SWTP and 1 unit of ISWTP within 5 years. Keywords: solid waste management system, 3R method, 3R-SWTS, ISWTP, Padang Pariaman Regency  ABSTRAK  Penelitian ini bertujuan untuk mengetahui kondisi eksisting pengelolaan sampah di Kabupaten Padang Pariamandan permasalahan yang dihadapi, serta mengkaji potensi penerapan sistem pengelolaan sampah kota dengan pendekatan metode reduce-reuse-recycle (3R) melalui sistem pengelolaan sampah berbasis Tempat Pengolahan Sampah (TPS3R)untuk skala kawasan dan Tempat Pengolahan Sampah Terpadu (TPST) untuk skala kota sebagai solusi permasalahan sampah kota kedepan. Studi ini dilakukan melalui survey, observasi dan wawancara dengan lembaga pengelola sampah, pengumpulan data skunder pengelolaan sampah dan studi literatur. Dari survey, observasi, dan wawancara diketahui bahwa timbulan sampah Kabupaten Padang Pariaman sebesar 1.396 m3/hari dan hanya1,35% sampah yang terlayani.Permasalahan pengelolaan sampah yang dihadapi adalah besarnya timbulan sampah yang tidak terlayani, sarana dan prasarana teknis operasional penanganan sampah yang belum memadai serta rendahnya praktik minimisasi sampah. Melalui penerapan sistem pengelolaan sampah berbasis TPS3R dan TPST diperkirakan akan dapat meminimisasisampah kota sebesar23% dengan operasional 7 buah TPS3R dan 1 buah TPST dalam jangka waktu 5 tahun. Kata Kunci: Sistem pengelolaan sampah, metode 3R, TPS3R, TPST, Kabupaten Padang Pariaman